Crystalline Carbosilane‐Based Block Copolymers: Synthesis by Anionic Polymerization and Morphology Evaluation in the Bulk State. Issue 3 (20th July 2022) - Hübner, Hanna; Niebuur, Bart‐Jan; Janka, Oliver; Gemmer, Lea; Koch, Marcus; Kraus, Tobias; Kickelbick, Guido; Stühn, Bernd; Gallei, Markus
Abstract: Block copolymers (BCPs) in the bulk state are known to self‐assemble into different morphologies depending on their polymer segment ratio. For polymers with amorphous and crystalline BCP segments, the crystallization process can be influenced significantly by the corresponding bulk morphology. Herein, the synthesis of the amorphous‐crystalline BCP poly(dimethyl silacyclobutane)‐ block ‐poly(2vinyl pyridine), (PDMSB‐ b ‐P2VP), by living anionic polymerization is reported. Polymers with overall molar masses ranging from 17 400 g to 592 200 g mol −1 and PDMSB contents of 4.8–83.9 vol% are synthesized and characterized by size‐exclusion chromatography and NMR spectroscopy. The bulk morphology of the obtained polymers is investigated by means of transmission electron microscopy and small angle X‐ray scattering, revealing a plethora of self‐assembled structures, providing confined and nonconfined conditions. Subsequently, the influence of the previously determined morphologies and their resulting confinement on the crystallinity and crystallization behavior of PDMSB is analyzed via differential scanning calorimetry and powder X‐ray diffraction. Here, fractionated crystallization and supercooling effects are observable as well as different diffraction patterns of the PDMSB crystallites for confined and nonconfined domains. Abstract : A novel synthesis route for block copolymers (BCP) consisting of a crystalline and an amorphous polymer segment, poly(dimethyl silacyclobutane)‐ block ‐poly(2‐vinylpyridine), is described. The resulting polymers are characterized with respect to their thermal and crystalline properties in the bulk state. The results show a strong dependency of the self‐assembled microstructures on the crystallization capabilities inside their confined BCP domains.